Evidence for an Interaction Between NEDD4 and Childhood Trauma on Clinical Characters of Schizophrenia With Family History of Psychosis - Bi, Xiao-Jiao; Hu, Lei; Qiao, Dong-Dong; Han, Chao; Sun, Meng-Meng; Cui, Kai-Yan; Wang, Li-Na; Yang, Li-Min; Liu, Lan-Fen; Chen, Zhe-Yu (Frontiers in Psychiatry, 2021)
Neural precursor cell-expressed developmentally downregulated 4 (NEDD4) polymorphisms and childhood trauma (CT) are associated with schizophrenia. However, whether NEDD4 interacts with CT on schizophrenic symptoms remains unknown. This study aimed to investigate the gene–environment interaction effect. Methods We recruited 289 schizophrenia patients and 487 controls and genotyped rs2303579, rs3088077, rs7162435, rs11550869, and rs62043855 in their NEDD4 gene. Results We found significant differences in the rs2303579 and rs3088077 between the two groups. Patients with the rs2303579 CC genotype had higher scores compared with other genotype (P = 0.026) in the test of positive schizophrenia syndrome scores, whereas patients with the rs3088077 TT (P = 0.037) and rs7162435 CC genotypes (P = 0.009) had higher scores compared with the other genotypes in the test of excitement factor. Patients with a family history of psychosis (FH+) reported higher negative scores (P = 0.012) than those without. Patients exposed to physical abuse (PA) reported a lower language learning and memory score (P = 0.017) and working memory score (P = 0.047) than those not. Patients exposed to sexual abuse (SA) reported a lower reasoning and problem-solving skills score (P = 0.025); those exposed to emotional neglect (EN) reported a lower social cognition score (P = 0.044); and those exposed to physical neglect reported a lower social cognition score (P = 0.036) but higher visual learning and memory score (P = 0.032). Rs3088077 could interact with EN to increase risk for schizophrenia. Optimal model rs62043855×EA, rs3088077×rs7162435×rs11550869×SA×EN and rs2303579×rs7162435×rs11550869×rs62043855×EA×PA could explain positive symptom, excitement symptom and working memory respectively in FH+ group. Conclusion The study highlighted that the combined interaction of NEDD4 and CT may be associated with schizophrenic symptoms especially for those with FH+.